2014
DOI: 10.1152/ajpendo.00146.2013
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial fragmentation impairs insulin-dependent glucose uptake by modulating Akt activity through mitochondrial Ca2+ uptake

Abstract: Insulin is a major regulator of glucose metabolism, stimulating its mitochondrial oxidation in skeletal muscle cells. Mitochondria are dynamic organelles that can undergo structural remodeling in order to cope with these ever-changing metabolic demands. However, the process by which mitochondrial morphology impacts insulin signaling in the skeletal muscle cells remains uncertain. To address this question, we silenced the mitochondrial fusion proteins Mfn2 and Opa1 and assessed insulin-dependent responses in L6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 37 publications
2
49
0
Order By: Relevance
“…14 Furthermore, mitochondrial fission results in an impaired insulin-dependent glucose uptake. 15 These findings suggest that leptin lowers blood glucose levels and may alter mitochondrial function by regulating PGC-1α. However, the mechanism by which leptin improves glucose uptake is unknown.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…14 Furthermore, mitochondrial fission results in an impaired insulin-dependent glucose uptake. 15 These findings suggest that leptin lowers blood glucose levels and may alter mitochondrial function by regulating PGC-1α. However, the mechanism by which leptin improves glucose uptake is unknown.…”
Section: Introductionmentioning
confidence: 92%
“…21 Insulin stimulates mitochondrial fragmentation and Ca 2+ uptake, and promotes Akt activation and mitochondrial glucose uptake to produces energy. 15 Mitochondrial fusion proteins are potent modulators of mitochondrial carbohydrate metabolism with an impact on energy metabolism in liver and skeletal muscle. However, the association between mitochondrial fusion and lipid metabolism is unclear.…”
Section: Mitochondria Play Critical Roles In Energy Production and Mementioning
confidence: 99%
“…IP 3 R phosphorylation by Akt, in addition to regulating sensitivity to apoptosis by preventing mitochondrial Ca 2+ overload, also provides negative feedback to the insulin signalling cascade. Recently we have shown that mitochondrial Ca 2+ uptake is crucial for effective insulin signaling in skeletal muscle cells [79] and cardiac myocytes [80]. Pharmacological inhibition of mitochondrial Ca 2+ uptake reduces insulin-dependent Akt phosphorylation, Glucose transporter 4 (GLUT4) membrane translocation and glucose uptake in these cells [79,80].…”
Section: Er-mitochondria Contact Sites and Cellular Signalingmentioning
confidence: 99%
“…In a recent work, we showed that mitochondrial fragmentation decreases Ca 2+ uptake, which is associated with mitochondrial dysfunction and impaired insulin signaling. 23 Therefore, we addressed the question as to whether the Dex-induced morphologic changes in mitochondria would affect mitochondrial Ca 2+ uptake. Figure 3C shows that Dex treatment for 6 h followed by histamine incubation enhanced Ca 2+ release into the cytosol.…”
Section: Dex Induces Mitochondrial Fragmentationmentioning
confidence: 99%